The unexpected emotional cost of teaching chemistry in a pandemic - Jones, Rebecca M. (Frontiers in Education, 2023)
In the past 2.5 years, STEM faculty around the world have faced unprecedent challenges, complete upheaval of routine, and staggering loss. Managing these new realities has required significant emotional labor. This paper offers one perspective on the emotional reality of teaching collegiate chemistry at a large public research university in the United States. Considering and describing emotions such as frustration, grief, anger and hope, I share a hidden reality of being faculty during a pandemic. I also discuss how we might learn from the path traveled and more deftly navigate the road ahead.